Effect of silica fertilizer on accumulation of phytolith in rice plant and soil - Phakeenuya Vanarat; Jose Diana; Kunmanee Punyanuch; Sanyapeung Marsuton; Pongprayoon Wasinee; Katam Keerthi; Sriariyanun Malinee (E3S Web of Conferences)
Phytoliths, silica structures formed in plant tissues, significantly contribute to carbon capture by stabilizing organic carbon within their structures and aiding long-term carbon sequestration in soils. Phytoliths play a crucial role in enhancing plant resistance to biotic and abiotic stresses and improving soil properties. This study investigates the impact of two types of silica fertilizers—silicic acid and sodium metasilicate —on the accumulation of phytoliths in rice plants and soil. The experiment was conducted under controlled conditions, with rice plants, RD43 cultivar, receiving applications of either silicic acid or sodium metasilicate at the ratio of 0.33 g/kg-soil. Results indicated a significant increase in phytolith content in both the rice plant tissues (3.76 and 2.79 fold) after applications of silicic acid and sodium metasilicate, respectively. Similarly, in the surrounding soil, accumulations of phytolith contents increased 3.50 and 1.90 fold compared to control soil, without addition of silica fertilizers. Silicic acid was found to be more effective in enhancing phytolith accumulation in rice tissues, while sodium metasilicate showed a greater impact on plant growth and yield. These findings suggest that the type of silica fertilizer used can influence the distribution and accumulation of phytoliths in plants and soils. The study underscores the importance of selecting appropriate silica fertilizers for sustainable rice cultivation and soil management practices.